Pengembangan teknik penentuan kombinasi penggunaan input-input produksi yang optimal: Studi Kasus KJA di Danau Maninjau, Kabupatan Agam, Sumatera Barat - Mohammad Noor (Economic Journal of Emerging Markets, 2001)
The objective of this research was to develope the formulation (equation) to estimate the optimal combination of production inputs used on the cage fish culture operation that most rational and harmonious, and consistent either to the theories of research results.